Peran guru dalam implementasi menejemen kelas SMP di pondok pesantren - Saiful Aziz; Santi Lisnawati (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2022)
To improve the quality of education, it is necessary to improve and improve education which is closely related to improving the quality of the operational teaching and learning process that takes place in the classroom. Therefore, good classroom management is needed so that learning objectives can be achieved. In Classroom Management, the teacher as the main actor who really determines the success or failure of students in learning, must always pay attention and create a conducive atmosphere in the classroom. With competent and qualified teachers, it is hoped that they will be able to create an effective learning atmosphere in the classroom. The problems that can be formulated are (1) how to implement classroom management in the teaching and learning process starting from planning and implementation (2) What are the inhibiting and supporting factors, and (3) what are the strategies to improve the teaching and learning process. Data collection is done by means of observation. The data analysis was carried out by descriptive qualitative analysis, namely by describing and analyzing all field data and then making conclusions. The results of this study are expected to be able to provide understanding to prospective teachers and become an evaluation for teachers that the importance of classroom management in order to improve the quality of the teaching and learning process so as to achieve a predetermined goal.AbstrakUntuk meningkatkan mutu pendidikan, diperlukan peningkatan dan penyempurnaan dalam pendidikan yang berkaitan erat dengan peningkatan mutu Proses Belajar Mengajar secara operasional yang berlangsung di dalam kelas. Oleh karena itu, diperlukan Manajemen kelas yang baik agar tujuan pembelajaran dapat tercapai. Dalam Manajemen Kelas, guru sebagai pemeran utama yang sangat menentukan berhasil tidaknya siswa dalam belajar, harus senantiasa memperhatikan dan menciptakan suasana kondusif di dalam kelas. Dengan adanya guru yang berkompeten dan berkualitas diharapkan mampu dalam menciptakan suasana belajar yang efektif di dalam kelas. Adapun masalah yang dapat dirumuskan adalah (1) bagaimana implementasi manajemen kelas dalam proses belajar mengajar yang dimulai dari perencanaan dan pelaksanaan (2) Apa faktor penghambat dan pendukungnya, dan (3) bagaimana strategi untuk meningkatkan proses belajar mengajar. Pengumpulan data dilakukan dengan cara observasi. Adapun analisis data dilakukan dengan deskriptif kualitatif analitik yaitu dengan cara mendeskripsikan dan menganalisis semua data lapangan kemudian membuat kesimpulan. Hasil penelitian ini diharapkan mampu memberikan pemahaman pada calon guru dan menjadi evaluasi bagi guru bahwasanya betapa pentingnya manajemen kelas dalam rangka meningkatkan kualitas proses belajar mengajar sehingga tercapai suatu tujuan yang telah ditentukan.